Multiresidue determination and predicted risk assessment of contaminants of emerging concern in marine sediments from the vicinities of submarine sewage outfalls - dos Santos, Dayana M. [UNESP]; Buruaem, Lucas [UNESP]; Gonçalves, Renato M. [UNESP]; Williams, Mike; Abessa, Denis M.S. [UNESP]; Kookana, Rai; de Marchi, Mary Rosa R. [UNESP] (Elsevier, 2018)
Submarine sewage outfalls (SSOs) are considered the main input source of contaminants of emerging concern continuously released in coastal areas, with the potential to cause adverse effects for aquatic organisms. This work presents the investigation of nine endocrine disrupting chemicals (EDCs) and 26 pharmaceutically active chemicals (PhACs) in marine sediments within the vicinities of 7 SSOs along the São Paulo State Coast (Brazil). Method optimization for the multi-residue determination by GC–MS/MS and LC-MS/MS using QuEChERS extraction/clean-up are discussed. Results demonstrate the occurrence of EDCs in concentrations ranging from less than method quantification limits (MQL) to 72.5 ng g−1 in sediments. All PhACs were <MQLs. Nonylphenol was the most ubiquitous compound and the diversity of EDCs increased with an increase in populations serviced by SSOs. The predicted environmental risk assessment considering measured environmental concentrations and ecotoxicity endpoints from literature suggest a high-risk potential in some of the investigated SSOs.
Keywords: Emerging contaminants; Risk assessment; Sediment